The Institutional Practice On nursing homes and hospitalizations - Ågotnes, Gudmund (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2017)
The nursing home resident of today is old and frail. Despite such a frailty, many residents are hospitalized, often with the intention of life-extension. Furthermore, rates of hospitalization varies considerably between countries, regions and institutions, even within smaller geographical areas. Even though relating to the same structural framework and conditions, distance to hospitals for instance, some nursing homes hospitalize considerably more than others.